Basic Psychological Needs Satisfaction and School Well-Being in Students - Alwi, M. Ahkam; Razak, Ahmad; Ridfah, Ahmad (Indonesian Journal of Educational Studies, 2023)
Low school well-being is still experienced by students which can have an impact on low academic outcomes. One factor that can improve school well-being is basic psychological needs satisfaction at school. The purpose of this study is to determine the relationship between basic psychological needs Satisfaction at School with school well-being in students. The subjects of the study were 300 X students in Makassar. The criteria for the research subjects are students of the class of 2022, the Bugis tribe and the Makasaar tribe, willing to be research respondents. Research sampling technique using Multistage non random sampling. Data collection using 2 scales, namely the questionnaire used is the research instrument used is the Brief Adolescents' Subjective Well-Being in School Scale version Indonesian (BASWBSS). and basic Psychological Needs at School Scale (ASBPNSS). Hypothesis testing of this study uses simple regression data analysis techniques using the help of SPSS. The results showed a positive relationship between basic psychological needs Satisfaction at School with school well-being in students.